FINANCIAL FEASIBILITY ANALYSIS OF PROCESSED CHOCOLATE BUSINESSAT TWINS CHOCOLATE HOME INDUSTRY IN PALU CITY - Abrar Abrar; Lien Damayanti; Yulianti Kalaba (AGROLAND: The Agricultural Sciences Journal, 2017)
Cocoa Agribusiness in Central Sulawesi still confronts many complex problems, such as low productivity due to PKB pests, low production quality. This becomes a challenge as well as investment opportunities in developing the business of chocolate product and achieve greater added value than cocoa agribusiness. This research  aimed to know the income and financial feasibility obtained by Twins Chocolate Industry chocolate product production in Palu. The research was conducted at the Twins Chocolate Industry Jalan Rusa No. 13 Talise subdistrict Mantikulore Palu city Central Sulawesi on October to September 2016. The respondents consisted of one leader and two employees in the field of production and marketing. The results showed that the revenue obtained in the first year was Rp 25.7017 million, the second year was Rp 26.8927 million and in the third year was Rp 38,309,875. Feasibility levelsobtained by the PP for 2 Years  and 2 Months were NPV Rp 11,927,788, an IRR of 22.75% and PI of 1.19. It means that Twins Chocolate industry was laboured because it met the eligibility criteria set.